Clinical effects of modified Halo-pelvic traction in patients with severe spinal deformities and respiratory disorders - Yunfei Yang; Lijun Huang; Guofeng Zhao; Jiyuan Xia; Xinqi Tian; Chang Liu; Qingfu Xia (Journal of Orthopaedic Surgery and Research)
Abstract Objective Effects of first-stage Halo-pelvic traction (HPT) combined with second-stage surgery in patients with severe scoliosis and pulmonary insufficiency. Methods A retrospective analysis was conducted on the clinical data of 100 patients with scoliosis and pulmonary insufficiency admitted to the Beijing Da Wang Road Emergency Rescue Hospital from January 2021 to October 2024. All patients underwent primary HPT traction treatment and secondary scoliosis correction surgery. Changes in imaging and lung function indicators of patients before traction, after the last traction follow-up, and after internal fixation surgery. Pearson’s statistical correlation analysis was used to investigate the effect of the Cobb angle of the principal curvature on lung function indicators. Results The lung function results of the included patients showed that restrictive ventilation function parameters increased to varying degrees (P < 0.05) before traction, during the last traction follow-up, and after the internal fixation surgery. Correlation analysis showed that as the Cobb angle of the main bend decreased, there was a significant negative correlation between lung restrictive ventilation function parameters (P < 0.05). Conclusion HPT traction can effectively correct severe scoliosis and improve respiratory function, making it a safe and effective adjunctive treatment.